1992
DOI: 10.1007/bf00155910
|View full text |Cite
|
Sign up to set email alerts
|

VLA and Trieste observations of type I storms, type IV and pulsations

Abstract: A prime objective of this experiment was to determine whether type I or IV sources at 333 MHz contain features of small (arc sec) scale. With the VLA, our resolution was better than 4". However, we never observed any structure of size smaller than about 30", with the typical source sizes being between about 40" and 90".Many observations were simultaneous with the Trieste Astronomical Observatory records at 327 MHz. The observations were made on two days in November 1988. On 8 November the observations were of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 20 publications
2
13
0
Order By: Relevance
“…Three noise storms were present, and Mercier et al gave results for the most intense storm. Because of the difficult intercalibration between both instruments, the accepted baselines were limited to about 6000 λ. Sizes of ∼50 arcsec were reported, in general agreement with the results of Zlobec et al (1992).…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…Three noise storms were present, and Mercier et al gave results for the most intense storm. Because of the difficult intercalibration between both instruments, the accepted baselines were limited to about 6000 λ. Sizes of ∼50 arcsec were reported, in general agreement with the results of Zlobec et al (1992).…”
Section: Introductionsupporting
confidence: 89%
“…Zlobec et al (1992) reported sizes ∼50 arcsec for about 20 bursts, with a minimum reliable value of 40 arcsec for two of them. Kerdraon et al (1988) also reported two bursts with size of 40 arsec.…”
Section: Apparent Sizes Of Noise Storm Coresmentioning
confidence: 94%
“…However, the observed position of solar radio sources may deviate from the original position because of coronal effects. Coronal scattering was proposed to produce the observed source size of typically between 40 and 90 at 333 MHz (Zlobec et al 1992). Figure 3 suggests that the position differences are not caused by an entirely random process.…”
Section: Discussionmentioning
confidence: 97%
“…We therefore adopt the smallest observed source size of 49″ in these maps to be a canonical number for comparison with our model predictions. The only other twodimensional map showing small source sizes that we are aware of is that of Zlobec et al [1992], who observed a source as small as 30″ at 327 MHz. However, the dynamic 1 Indian Institute of Science Education and Research, Pune, India.…”
Section: Introductionmentioning
confidence: 97%